Comparing Teacher Professional Development Effectiveness Across High-Performing PISA Systems: A Cross-Continental Policy Analysis Using the New World Kirkpatrick Model - Inu Eka Nugraha; Iman Subasman; Moh Firdaos Agih; Dodi Suhendi; Syibli Maufur; M Syamsul Ma'arif; Aini Mazaya El Banna (Journal of Education Research, 2026)
This study examines why several education systems sustained high learning performance following the global disruption caused by the COVID-19 pandemic, while many others experienced substantial learning loss. It aims to compare how teacher professional development is translated into classroom practice across four high-performing PISA 2022 systems representing different continents: Singapore, Estonia, Ontario (Canada), and Australia. A qualitative descriptive approach employing comparative policy analysis was adopted, with the New World Kirkpatrick Model serving as the analytical framework to examine training effectiveness across the dimensions of reaction, learning, behavior, and results. The analysis demonstrates that although all four systems have well-established professional learning structures, their distinguishing strength lies in the institutional mechanisms that facilitate behavioral transfer after training. These mechanisms include instructional leadership, professional collaboration, performance monitoring, and transparent career progression. The study concludes that sustainable educational excellence depends not merely on the quality of teacher training but on coherent performance management systems that systematically connect professional learning with instructional practice and long-term educational outcomes.